Endotracheal tube cuff pressure in three hospitals, and the volume required to produce an appropriate cuff pressure - Sengupta, Papiya (BioMed Central, 2004)
BACKGROUND: Cuff pressure in endotracheal (ET) tubes should be in the range of 20–30 cm H(2)O. We tested the hypothesis that the tube cuff is inadequately inflated when manometers are not used. METHODS: With IRB approval, we studied 93 patients under general anesthesia with an ET tube in place in one teaching and two private hospitals. Anesthetists were blinded to study purpose. Cuff pressure in tube sizes 7.0 to 8.5 mm was evaluated 60 min after induction of general anesthesia using a manometer connected to the cuff pilot balloon. Nitrous oxide was disallowed. After deflating the cuff, we reinflated it in 0.5-ml increments until pressure was 20 cmH(2)O. RESULTS: Neither patient morphometrics, institution, experience of anesthesia provider, nor tube size influenced measured cuff pressure (35.3 ± 21.6 cmH(2)O). Only 27% of pressures were within 20–30 cmH(2)O; 27% exceeded 40 cmH(2)O. Although it varied considerably, the amount of air required to achieve a cuff pressure of 20 cmH(2)O was similar with each tube size. CONCLUSION: We recommend that ET cuff pressure be set and monitored with a manometer.